Enhancement of mitochondrial calcium uptake is cardioprotective against maladaptive hypertrophy by retrograde signaling uptuning Akt - Tania Zaglia; Antonio Campo; Nicola Moro; Vittoria Di Mauro; Giulia Borile; Roberta Menabò; Salvatore Antonucci; Laura Poli; Marika Campesan; Pierluigi Carullo; Sara Martinazzi; Giovanni B. Luciani; et al. (Proceedings of the National Academy of Sciences, 2025)
Regulation of mitochondrial Ca 2+ uptake is critical in cardiac adaptation to chronic stressors. Abnormalities in Ca 2+ handling, including mitochondrial uptake mechanisms, have been implicated in pathological heart hypertrophy. Enhancing mitochondrial Ca 2+ uniporter (MCU) expression has been suggested to interfere with maladaptive development of heart failure. Here, we addressed whether MCU modulation affects the cardiac response to pressure overload. MCU content was quantified in human and murine hearts at different phases of myocardial hypertrophy. Cardiac function/structure were analyzed after Transverse Aortic Constriction (TAC) in mice undergone viral-assisted overexpression or downregulation of MCU. In vitro and ex vivo assays determined the effect of MCU modulation on mitochondrial Ca 2+ uptake, cellular phenotype and hypertrophic signaling. In human and murine hearts MCU levels increased in the adaptive phase of myocardial hypertrophy and declined in the failing stage. Consistently, modulation of MCU had a cell-autonomous effect in cardiomyocyte/heart adaptation to chronic overload. Indeed, upon TAC MCU-downregulation accelerated development of contractile dysfunction, interstitial fibrosis and heart failure. Conversely, MCU-overexpression prolonged the adaptive phase of hypertrophic response, as, in advanced stages upon TAC, hearts showed preserved contractility, absence of fibrosis and intact vascularization. In vitro and ex vivo analyses indicated that enhancement in mitochondrial Ca 2+ uptake in cardiomyocytes entails “mitochondrion-to-cytoplasm” signals leading to ROS-mediated activation of Akt, which may explain the protective effects towards heart response to TAC. Enhanced mitochondrial Ca 2+ uptake affects the compensatory response to pressure overload via retrograde mitochondrial-Ca 2+ /ROS/Akt signaling, thus uncovering a potentially targetable mechanism against maladaptive myocardial hypertrophy.